2017
DOI: 10.1177/1177272716689818
|View full text |Cite
|
Sign up to set email alerts
|

Expression is Down-Regulated by Oxidative Stress in Endometriosis and Endometriosis-Associated Ovarian Cancer

Abstract: Oxidative stress is considered an important factor in the development of endometriosis, including its malignant transformation. Previous studies have found that AT-rich interactive domain 1A (ARID1A), a tumor suppressor gene, is frequently mutated and inactivated in endometriosis-associated ovarian cancer (EAOC), and such a change in this gene is considered an early event in malignant transformation. We observed oxidative stress status by measuring the activity of the antioxidant enzyme manganese superoxide di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Glutathione constitutes the survival advantage for cancer cells and is required for cancer initiation and progression (37,38). To date, a number of studies have demonstrated that the oxidant-antioxidant imbalance plays a critical role in the initiation and progression of multistage carcinogenesis of endometriosis (23,30,(39)(40)(41). These studies support the redox imbalance hypothesis that there are at least two stages of iron carcinogenesis and tumor progression: The initial wave of iron-induced oxidative stress would be followed by the second big wave of subsequent synthesis of the antioxidants, which diminishes cellular oxidative stress capacity, increases apoptosis resistance and promotes tumor initiation and progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione constitutes the survival advantage for cancer cells and is required for cancer initiation and progression (37,38). To date, a number of studies have demonstrated that the oxidant-antioxidant imbalance plays a critical role in the initiation and progression of multistage carcinogenesis of endometriosis (23,30,(39)(40)(41). These studies support the redox imbalance hypothesis that there are at least two stages of iron carcinogenesis and tumor progression: The initial wave of iron-induced oxidative stress would be followed by the second big wave of subsequent synthesis of the antioxidants, which diminishes cellular oxidative stress capacity, increases apoptosis resistance and promotes tumor initiation and progression.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, steroidogenic factor-1 (SF-1), a transcriptional factor essential for estrogen biosynthesis, has been shown to be hypomethylated and aberrantly expressed (51). Furthermore, oxidative stress (exogenous H 2 O 2 ) downregulates ARID1A mRNA and protein expression (39,52,53). Oxidative stress recruits DNA methyltransferase to chromatin (54), and also modifies the expression of CpG demethylases, such as ten-eleven translocation (TET) and jumonji (JMJ) genes (49).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…Partial loss of ARID1A staining (ie, in one tissue section some cells are stained positive while others are negative) has been reported to be in 36% (9/25) of rectovaginal DE samples . ARID1A gene expression levels in endometriosis are significantly lower than that of control endometrium, and oxidative stress downregulates ARID1A . Incidentally or not, loss of chromosome 1p36.12, where the ARID1A locus is located, also was reported in both ectopic and eutopic endometrium from a woman with SPE …”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their mentioning
confidence: 99%
“…48 ARID1A gene expression levels in endometriosis are significantly lower than that of control endometrium, and oxidative stress downregulates ARID1A. 206 Incidentally or not, loss of chromosome 1p36.12, where the ARID1A locus is located, also was reported in both ectopic and eutopic endometrium from a woman with SPE. 31 Tissue regeneration or repair has been reported to resemble the embryonic developmental process since both processes undergo reorganization and rearrangement of tissue architecture concomitant with distinct transcriptional patterns.…”
Section: Arid1amentioning
confidence: 99%
“…Белки семейства Kruppel-like factors (KLF) играют важную роль в процессах клеточной пролифера-ции, выживания, дифференцировки; KLF4 и KLF15 принимают участие в пролиферации эндометрия, моделируя сигналы эстрогена и прогестерона [28]. [29] подтвердили сниженную экспрессию гена ARID1A у женщин с эндометриоз-ассоциированным бесплодием и связали ее с персистирующим окислительным стрессом, наблюдаемым при данном заболевании.…”
unclassified